2015
DOI: 10.12779/dnd.2015.14.4.176
|View full text |Cite
|
Sign up to set email alerts
|

Anti-N-Methyl-D-Aspartate Receptor Encephalitis Presenting Progressive Dyslexia: A Case Report

Abstract: Background Anti-N-methyl-D-aspartate (anti-NMDA) receptor encephalitis was discovered less than 10 years ago. Its symptoms and characteristics are not well-defined yet. We experienced a case of anti-NMDA receptor encephalitis with phonemic paraphasia and acalculia that were not classical characteristics. Case Report A 44-year-old woman started to show dyslexia, phonemic paraphasia, and dyscalculia. These symptoms were gradually worsening for over 30 days. Various brain images were not helpful for primary diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The authors specifically investigated mathematic computations with the TMT-A and B, reporting intact performance respect to the premorbid status. In another paper [9], the authors reported the case of a 44-year-old mathematics teacher affected by NMDA encephalitis, that presented dyslexia, phonemic paraphasia, and dyscalculia. In this person all symptoms improved gradually after treatment and, 6 months later, she was able to go back to teach students.…”
Section: Discussionmentioning
confidence: 99%
“…The authors specifically investigated mathematic computations with the TMT-A and B, reporting intact performance respect to the premorbid status. In another paper [9], the authors reported the case of a 44-year-old mathematics teacher affected by NMDA encephalitis, that presented dyslexia, phonemic paraphasia, and dyscalculia. In this person all symptoms improved gradually after treatment and, 6 months later, she was able to go back to teach students.…”
Section: Discussionmentioning
confidence: 99%